Fiscal deficit reduction programs in developing countries: Stabilization versus growth in the presence of credit rationing - Cuddington, John T. (Estudios Económicos de El Colegio de México, 1992)
This paper presents a model for analyzing potential conflicts between short-run output and employment effects and medium-run growth effects of various fiscal actions. In the model, both firms and households are intertemporal optimizers; short-run wage stickiness and interest rate controls generate macroeconomic disequilibrium. The analysis focuses on the consequences of various government expenditure or deficit reduction policies.